Meningkatkan Aktivitas Dan Prestasi Belajar IPA Melalui Model Pembelajaran Make-A Match Siswa Di SDN 033 Senama Nenek Kecamatan Tapung Hulu - Zahrona Tambunan (Universitas Maritim AMNI Semarang, 2024)
To improve the quality of the student learning process by increasing the quality of teachers' professional abilities, all teachers must go through a learning process that makes it possible to find and solve learning problems in their respective classes based on the principles of Classroom Action Research (PTK). Classroom Action Research is carried out with the aim of improving or enhancing student learning activities and achievements. PTK is an activity carried out to find out problems that arise in the classroom when the teacher is interacting with students in carrying out the teaching and learning process. PTK is research carried out by class teachers through self-reflection with the aim of improving teacher performance, so that the quality of learning increases (Mills, Geoffrey E, 2000, Schmuch, A. Richard, 1997) which can be seen in the percentage of students' success in completing the exercises systematically. verbally and in writing. In the learning process, learning means an activity carried out by the teacher and students together. The essence of the learning is the process of giving and receiving and ends with an evaluation which is deliberately carried out by the teacher to find out how far the students' level of understanding is